Inovasi Kurikulum: Keseimbangan Pendidikan di Pesantren - Rois Mahmudi; M. Imam Khaudli (Journal of Innovative and Creativity, 2025)
This study aims to examine how curriculum innovation in Islamic boarding schools can create an educational balance between traditional values ​​and the demands of the modern era. The approach used is qualitative with a case study research type conducted at the Darussalam Blokagung Islamic Boarding School in Banyuwangi, one of the largest and oldest Islamic boarding schools in Banyuwangi that has implemented various curriculum innovations by integrating religious and general education. Data collection techniques include observation, in-depth interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The validity of the data was tested through triangulation of sources and techniques. The results of the study indicate that curriculum innovation in Islamic boarding schools is able to encourage the relevance of this institution in the digital era, shape the character of inclusive and tolerant students, and prepare them as digital actors in preaching and social education. This study contributes to the development of a curriculum model for Islamic boarding schools that is responsive to developments in the era without leaving a strong Islamic identity. Keywords: Innovation, Curriculum, Educational Balance, Islamic Boarding Schools